High-carbohydrate diets and insulin-dependent diabetics. Issue 6189 (1st September 1979) - Simpson, R W; Mann, J I; Eaton, J; Carter, R D; Hockaday, T D
Abstract : A high-carbohydrate-(HC)-modified fat diet was compared with a standard low-carbohydrate (LC) diabetic diet in 11 insulin-dependent diabetics. Basal and preprandial plasma glucose concentrations were appreciably lower when the patients received the HC diet derived chiefly from readily available cereal and vegetable sources (mean (+/- SE of mean) basal concentrations 6.7 +/- 1.2 mmol/l (121 +/- 22 mg/100 ml) with the LC diet and 4.3 +/- 0.7 mmol/l (77 +/- 13 mg/100 ml) with the HC diet; mean preprandial concentrations 11.1 +/- 1.2 mmol/l (200 +/- 22 mg/100 ml) LC diet and 8.9 +/- 1.3 mmol/l (160 +/- 23 mg/100 ml) HC diet). total and low-density lipoprotein cholesterol concentrations were lower when patients took the HC diet (mean 4.4 +/- 0.2 and 2.4 +/- 0.2 mmol/l (189 +/- 8 and 124 +/- 8 mg/100 ml) respectively), and the ratio of high-density lipoprotein cholesterol to total cholesterol tended to rise. The average percentage of glycosylated haemoglobin did not differ between the two diets. Thus several measures of carbohydrate and lipid metabolism appear to be more satisfactory when patients receive a HC diet, which is an acceptable alternative to that still recommended to most insulin-requiring patients.